Siglecs as Immune Cell Checkpoints in Disease - Duan, Shiteng; Paulson, James C (Annual review of immunology, 2020)
Sialic acid-binding immunoglobulin-type lectins (Siglecs) are expressed on the majority of white blood cells of the immune system and play critical roles in immune cell signaling. Through recognition of sialic acid-containing glycans as ligands, they help the immune system distinguish between self and nonself. Because of their restricted cell type expression and roles as checkpoints in immune cell responses in human diseases such as cancer, asthma, allergy, neurodegeneration, and autoimmune diseases they have gained attention as targets for therapeutic interventions. In this review we describe the Siglec family, its roles in regulation of immune cell signaling, current efforts to define its roles in disease processes, and approaches to target Siglecs for treatment of human disease.